Intervensi Harga Produk Sekunder Pada Masa Pandemi Covid-19 Perspektif Islam - Nafilatur Rohmah Rohmah; Meichio Lesmana Lesmana; Ahmad Suminto Suminto (Islamic Economics Journal, 2021)
Islam applies freedom in the market mechanism on condition that it does not conflict with the values and principles of sharia. In the condition of the Covid-19 pandemic facing the world, especially Indonesia, the government must intervene in prices for internet data product prices because the PSBB policy implemented by the government to break the chain of spread of Covid-19 has a significant impact on public opinion, especially for the lower middle class. In addition, this policy will make the demand for internet data quite high while government subsidies cannot accommodate the community's need for internet data. The purpose of this study was to determine the Intervention of Secondary Product Prices during the Covid-19 Pandemic Period from an Islamic Perspective. The research used in this research is library research. The high market demand for the internet and the decline in people's incomes make the price of internet data difficult to reach by all levels of society, this requires the role of the government. the government can make decisions or regulations regarding the maximum limit for internet data prices during this pandemic period so that the selling price can be reached by all circles of society and still provide profits or profits for the seller or producer.